A Development and Validation of Heutagogical Survey Items - Mohamad, Mimi Mohaffyza; Barajing, Terancy; J, Sulaiman; Mohd Affendi, Haryanti; Raja Mohd Ali, Raja Haslinda (Journal of Technical Education and Training, 2023)
The development of survey items includes the preparing and validating the items.  A construct validity and reliability are two important concepts in survey research that are used to assess the quality of survey items. This study was conducted to generate on the construct validity process of the survey items in heutagogy elements specifically for vocational learning.  Items have been developed based on relevant literature and the context of vocational education in particular leads to readiness for employment. Therefore, to go through the process of validity and reliability of the items, this study involved 100 students from Vocational Colleges to response the survey items. There are 71 items in a set of questionnaires with six elements consists of Exploring, Collaborating, Relationship, Creating, Reflection and Sharing. The data was analysed based on Rasch Model as statistical measurement model that can be used to assess the validity and reliability of research instruments. The construct validity was examined by analysing the point-measure correlation index, infit, and outfit values; meanwhile, the reliability was examined by analysing the item reliability index. The results have shown that the findings of the analysis found seven items dropped because the items did not meet the requirements of the established analysis. By analysing the data collected from the questionnaire, the final instrument shows a total of 64 items suitable for measuring six elements of heutagogy. The Rasch Model differs from other measurement models in reliability assessment by focusing on one-dimensionality, assessing both person and item reliability, enabling item calibration, and providing fit statistics. Hence, this systematic approach may facilitate researcher to improve the items to produce the good quality of research instrument.